Evolution of permeability in a single granite fracture at high temperature. (15th April 2019) - Shu, Biao; Zhu, Runjun; Tan, Jingqiang; Zhang, Shaohe; Liang, Ming
Abstract: Thermal energy recovered from Hot Dry Rock (HDR) or Engineered Geothermal Systems (EGS) is clean and renewable and may fulfill current energy demands. The long term flow characteristic of fractures is a key issue related to both the rate of geothermal production and the service life of the geothermal reservoir. We explore the long term fluid transport characteristics of a long (50 mm wide and 300 mm long) artificial fracture in granite at temperatures to 200 °C. Permeability is measured under steady flow conditions in three stages: (1) stepped increments of temperature from 25 °C to 200 °C; (2) constant temperature of 200 °C applied for 27 h; (3) gradually decreased temperature from 200 °C to 25 °C. The evolution of hydraulic aperture and permeability of the fracture is evaluated over these three regimes. Hydraulic aperture and permeability decrease with the increase in temperature. Uniform high temperatures result in a continued but gradual reduction in both hydraulic aperture and permeability. The reduction in hydraulic aperture and permeability of the fracture is permanent with marginal recovery as the temperature is reset to the original 25 °C. Permeability and heat transfer efficiency increase during heating (stage 1), but decrease during high temperature production and then cooling (stages 2 and 3).